Helpful to Live Healthier? Intermittent Hypoxic/Ischemic Training Benefits Vascular Homeostasis and Lipid Metabolism with Activating SIRT1 Pathways in Overweight/Obese Individuals - Jiao, Xueqiao; Liu, Moqi; Li, Rui; Li, Jialu; Wang, Lu; Niu, Guowei; Wang, Liming; Ji, Xunming; Lv, Chunmei; Guo, Xiuhai (Obesity facts, 2024)
Introduction: The present study aimed to investigate whether and how normobaric intermittent hypoxic training (IHT) or remote ischemic preconditioning (RIPC) plus normoxic training (RNT) has a synergistic protective effect on lipid metabolism and vascular function compared with normoxic training (NT) in overweight or obese adults. Methods: A total of 37 overweight or obese adults (36.03 ± 10.48 years) were randomly assigned to 3 groups: NT group (exercise intervention in normoxia), IHT group (exercise intervention in normobaric hypoxic chamber), and RNT group (exercise intervention in normoxia + RIPC twice daily). All participants carried out the same 1-h exercise intervention for a total of 4 weeks, 5 days per week. Physical fitness parameters were evaluated at pre- and postexercise intervention. Results: After training, all three groups had a significantly decreased body mass index (p < 0.05). The IHT group had reduced body fat percentage, visceral fat mass (p < 0.05), blood pressure (p < 0.01), left ankle-brachial index (ABI), maximal heart rate (HRmax) (p < 0.05), expression of peroxisome proliferator-activated receptor-γ (PPARγ) (p < 0.01) and increased expression of SIRT1 (p < 0.05), VEGF (p < 0.01). The RNT group had lowered waist-to-hip ratio, visceral fat mass, blood pressure (p < 0.05), and HRmax (p < 0.01). Conclusion: IHT could effectively reduce visceral fat mass and improve vascular elasticity in overweight or obese individuals than pure NT with the activation of SIRT1-related pathways. And RNT also produced similar benefits on body composition and vascular function, which were weaker than those of IHT but stronger than NT. Given the convenience and economy of RNT, both intermittent hypoxic and ischemic training have the potential to be successful health promotion strategies for the overweight/obese population.